Impaired Circulating Antibody-Secreting Cells Generation Predicts the Dismal Outcome in the Elderly Septic Shock Patients - Xu H; Li T; Zhang X; Li H; Lv D; Wang Y; Huo F; Bai J; Wang C (Dove Medical Press, 2022)
Huihui Xu,1,2,* Teng Li,1,2,* Xiaoming Zhang,1,3 Hongqiang Li,4 Diyu Lv,4 Yiyuan Wang,4 Fangjie Huo,5 Jianwen Bai,4,6 Chunmei Wang4,6 1Key Laboratory of Molecular Virology and Immunology, Institut Pasteur of Shanghai, Chinese Academy of Sciences, Shanghai, 200031, People's Republic of China; 2University of Chinese Academy of Sciences, Beijing, 100000, People's Republic of China; 3Shanghai Huashen Institute of Microbes and Infections, Shanghai, 200052, People's Republic of China; 4Department of Emergency Medicine and Critical Care, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, 200120, People's Republic of China; 5Department of Respiratory Medicine, Xi'an No. 4 hospital, Xi'an, 710004, People's Republic of China; 6Department of Emergency Medicine and Critical Care, Shanghai East Hospital, Nanjing Medical University, Nanjing, Jiangsu Province, 211166, People's Republic of China*These authors contributed equally to this workCorrespondence: Chunmei Wang; Jianwen Bai, Department of Emergency Medicine and Critical Care, Shanghai East Hospital, Tongji University School of Medicine, 150 Jimo Road, Shanghai, 200120, People's Republic of China, Tel +8613761004402 ; +8613386057150, Email wcm1702@163.com; baijianwen1019@163.comPurpose: Sepsis is a condition that derives from a dysregulated host response to infection. Although B lymphocytes play a pivotal role in immune response, little is known about status of their terminally differentiated cells, antibody-secreting cells (ASCs) during immunosuppressive phase of sepsis, especially in elderly patients. Our aim was to extensively characterize the immune functions of ASCs in elderly septic patients.Patients and Methods: Clinical and laboratory data were collected on days 1, 3, and 7 of hospitalization. Circulating ASCs were evaluated by flow cytometry from fresh whole blood in elderly septic patients at the onset of disease. RNA sequencing analyzed ASCs gene expression profile. Receiver operating characteristic (ROC) curve analysis and logistic regression predicted the survival rate of 28-day mortality.Results: A total of 103 septic patients were enrolled. The number and proportion of ASCs among total lymphocytes dramatically increased in septic patients, and RNA sequencing analysis showed that ASCs from septic patients exhibited a different gene expression profile. Furthermore, we found these ASCs could promote the function of T cells. Logistic regression analysis showed ASCs population was an independent outcome predictor in septic shock patients.Conclusion: Our study revealed the complex nature of immune disorders in sepsis and identified circulating ASCs population as a useful biomarker for predicting mortality in elderly septic patients, which provided a novel clue to combat this severe disease.Keywords: biomarker, antibody-secreting cells, prognosis, sepsis, septic shock